DESIGN AND DEVELOPMENT POINT OF SALE SYSTEM WITH DSS (DECISION SUPPORT SYSTEM) USING SDLC RESEARCH METHOD - Muhammad Ardiansyah; Jukenly Jukenly (Universitas Internasional Batam, 2022)
The study was conducted to provide a complete and easy-to-use cashier service for MSMEs in Indonesia, because almost eighty percent of basic food stores in Indonesia are still done manually when entering data, causing the resulting data cannot be developed properly, and errors often occur. recording, and searching for data is difficult because every time you look for data, the seller must look for it from the general ledger. There is no special information that informs about the amount of stock of goods so that it is not uncommon when the stock runs out, the new shop owner finds out when the transaction process occurs so that it disappoints customers. With these weaknesses, a web-based cashier application is needed that can facilitate data management once it produces valid data so that it can be used to develop the company in the future. The method used is the waterfall method, in making the application starting from the analysis, design, coding, testing, evaluation, and maintenance stages.